Effects of the Municipal Solid Waste Landfill on the Quality of Water Resources in Khalkhal: A Case Study - Zahra Javanmardi; Morteza Alighadri; Saeed Parastar; Tayebe Sadeghi (Hamadan University of Medical Sciences, 2022)
Transmission of leachate from municipal solid waste landfills can potentially threaten ecosystems and human societies when the landfill has no system for collecting and treating leachate. Leachate produced from landfills finds its way through the soil to groundwater and surrounding surface waters, leading to pollution of water resources. This study aimed to investigate the effects of leachate from Khalkhal landfill (a city in Ardabil province, northwestern Iran) on the quality of groundwater and surrounding surface water. During 2019-2020, 4 wells (one control well located upstream of the landfill and three wells located downstream of the landfill) and two stations of the surface water resource of the Herochai river were spots for sampling. First, we did sampling during high and low rainfall seasons in accordance with the standards. Second, we analyzed the values of some physical, chemical, and biological quality parameters according to standard methods. The sampling of the soil texture was conducted following ASTM D 422 standards. Then, the soil was analyzed at Reference Laboratory of Water, Soil, and Plant in Ardabil province. The value of most parameters measured in the water of downstream wells was lower than the limit recommended by the Iranian and World Health Organization, indicating no limitation for drinking and agricultural uses. The quality of the Herochai river water was also relatively undesirable in terms of turbidity and total coliform in some samples. Additionally, consistent with the study results, no difference was observed between high and low rainfall seasons. According to the results obtained from different parameters, Schuler and Wilcox diagrams, and landfill water pollution index (LWPI), the quality of upstream and downstream water resources of Khalkhal municipal solid waste landfill was not much different. In other words, the landfill did not affect water.